A plant endophytic bacterium Burkholderia seminalis strain 869T2 increases plant growth under salt stress by affecting several phytohormone response pathways - Hau-Hsuan Hwang; Yu-Ting Huang; Pei-Ru Chien; Fan-Chen Huang; Chih-Lin Wu; Liang-Yu Chen; Shih-Hsun Walter Hung; I-Chun Pan; Chieh-Chen Huang (Botanical Studies)
Abstract Background Due to global warming and gradual climate change, plants are subjected to a wide range of environmental stresses, adversely affecting plant growth and production worldwide. Plants have developed various mechanisms to overpower these abiotic stresses, including salt stress, drought, and high light intensity. Apart from their own defense strategies, plants can get help from the beneficial endophytic bacteria inside host plants and assist them in enduring severe growth conditions. A previously isolated plant endophytic bacteria, Burkholderia seminalis 869T2, from vetiver grass can produce auxin, synthesize siderophore, and solubilize phosphate. The B. seminalis 869T2 can colonize inside host plants and increase the growth of bananas, Arabidopsis, and several leafy vegetables. Results We further demonstrated that different growth parameters of Arabidopsis and pak choi plants were significantly increased after inoculating the B. seminalis 869T2 under normal, salt, and drought stress conditions compared to the mock-inoculated plants. Both transcriptome analysis and quantitative real-time PCR results showed that expression levels of genes related to phytohormone signal transduction pathways, including auxin, gibberellin, cytokinin, and abscisic acid were altered in Arabidopsis plants after inoculated with the strain 869T2 under salt stress, in comparison to the mock-inoculated control with salt treatments. Furthermore, the accumulation levels of hydrogen peroxide (H2O2), electrolyte leakage (EL), and malondialdehyde (MDA) were lower in the 869T2-inoculated Arabidopsis and pak choi plants than in control plants under salt and drought stresses. Conclusions The plant endophytic bacterium strain B. seminalis 869T2 may affect various phytohormone responses and reduce oxidative stress damage to increase salt and drought stress tolerances of host plants.